Testing McLoughlin’s Trust Model on Turkish Information Technology Employees - Emrah Özsoy; Dominic Mcloughlin; Osman Uslu (İşletme Bilimi Dergisi)
Research purpose: The purpose of this study is to replicate McLoughlin’s (2014) Trust Model developed on the sample of knowledge workers in Australia. McLoughlin’ (2014) Trust Model includes variables such as trust reliance, trust disclosure, trust in organisation, change, perceived character of supervisors, communication, participation, organizational citizenship behaviour, job satisfaction, support for change direction, and affective commitment. Method: In this study all the variables were measured with the scales that were used in McLoughlin’ (2014) study on IT employees sample. 121 IT employees participated in this research from several organizations in Turkey.